Agriculture -based alternative livelihood for the depressed communities in Zamboanga del Norte - Nabua, Wilson C. (The Threshold: the Official Research Journal of Jose Rizal Memorial State University, Zamboanga del Norte, 2012)
Depressed communities in Zamboanga del Norte namely; La Libertad, Siayan, an Godod, are agricultural communities. The study identified low productivity as the main reason for the low income of the families in the communities. Low productivity in turn was linked to the farming practices, general topography of the farming communities and marketing practices. The paper proceeds to evaluate alternative agricultural production system as well as livelihood that hinge on agricultural food processing towards enhancing the economic productivity of these communities.